2020
DOI: 10.1016/j.jhin.2020.04.031
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19: how prepared are front-line healthcare workers in England?

Abstract: NHS) for the COVID-19 pandemic; however, the efficacy of these interventions is unknown. In view of this, a cross-sectional survey of front-line healthcare workers (HCWs) at two large acute NHS hospital trusts in England was undertaken to assess their confidence and perceived level of preparedness for the virus. The survey found that there has been moderate success in readying HCWs to manage COVID-19, but that more still needs to be done, particularly in relation to educating HCWs about laboratory diagnostics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
44
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(68 citation statements)
references
References 7 publications
4
44
0
2
Order By: Relevance
“…Even though some studies have looked at the HCWs' infection and psychological well-being, our study sought to assess the factors contributing to these outcomes. [13][14][15] Overall, our results corroborate presumptions regarding the correlation between various risk factors and HCW infection with more recent studies showing adequacy of PPE, clinical settings, gender and ethnic background as important factors of HCW infection. [22][23][24][25] Our sample of HCWs, overall had higher reported COVID-19 infection risk (29%) compared with general population estimates.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Even though some studies have looked at the HCWs' infection and psychological well-being, our study sought to assess the factors contributing to these outcomes. [13][14][15] Overall, our results corroborate presumptions regarding the correlation between various risk factors and HCW infection with more recent studies showing adequacy of PPE, clinical settings, gender and ethnic background as important factors of HCW infection. [22][23][24][25] Our sample of HCWs, overall had higher reported COVID-19 infection risk (29%) compared with general population estimates.…”
Section: Discussionsupporting
confidence: 90%
“…Additionally, few studies have looked at the association of factors such as PPE availability and testing, with subsequent COVID-19 infection in HCWs. [11][12][13][14][15] Finally, the association of these variables with psychological distress and clinician burn-out has not been described. While previous studies have broadly described occupational stressors and lack of availability of PPE for frontline providers, few studies have attempted to sample a broad range of both clinicians and non-clinical healthcare staff.…”
Section: Open Accessmentioning
confidence: 99%
“…These results challenge the inclination of our front-line healthcare workers to combat the prevailing circumstance. Another study showed that about 76% of the front-line healthcare workers had some level of confidence in isolating a suspected case while 72% of respondents of the study felt somewhat confident about what and how to use PPE [11]. The disparity in these percentages signifies that the level of training of doctors in our hospitals is notably unsatisfactory regarding PPE usage.…”
Section: Discussionmentioning
confidence: 91%
“…Different reasons have been described as a cause of COVID-19 spread among healthcare workers including inadequate availability of PPE due to international shortage, lack of knowledge, inadequate training, intensity of work and long-time exposure to infected patients. Another concept among healthcare workers is to protect their health by expanding COVID-19 screening tests among them in order to reduce the risk of transmission [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%